3D CAD data extraction and conversion for application of augmented/virtual reality to the construction of ships and offshore structures. Issue 7 (3rd July 2019) - Han, Young-Soo; Lee, Jaejoon; Lee, Jungmin; Lee, Wonhyuk; Lee, Kyungho
ABSTRACT: Due to the global economic downturn and low oil prices, orders for offshore plants and vessels have declined. Moreover, the range of regulations has increased and customer requirements have diversified. As a result, a new paradigm for the manufacturing environment is needed to improve competitiveness. As IT technology develops, we are making efforts to improve product design and production efficiency by combining various technologies such as digital twin, virtual reality and augmented reality. To use these technologies, 3D models of products are important. A product model exists in a 3D CAD system, which is required to utilize the model. The focus of previous research was on shape transformation using neutral formats such as igs and step files. However, this was also incomplete, and would be better visualized in virtual/augmented reality. In this study, we aimed to develop a framework to extract and visualize 3D models that could be used in augmented/virtual reality in real time and we conducted a test to verify the framework's validity and efficiency. As a result of the test, it is expected that this framework will be a valuable variety field in the lifecycles of a ship, an offshore structure, and an industrial plant.